Treatment of chronic heart failure with a very low dose of antibodies to C-fragment of type 1 angiotensin II receptor - T. M. Poponina; Ye. S. Noll; Yu. S. Poponina; B. F. Portnyagin; N. M. Simonova (Бюллетень сибирской медицины, 2009)
The open randomized placebo-controlled prospective study was conducted; we documented improvement of global contractility and diastolic function of left ventricle, clinical and psychological status in 60 patients with chronic heart failure receiving a very low dose of antibodies to C-end fragment to AT1 receptors of angiotensin II for 6 months (Cardosten). The drug was well-tolerated.